Basic 3D Animation Online Learning Model for Multimedia Student - I Made Marthana Yusa; I Ketut Ardhana; I Nyoman Darma Putra; Ida Bagus Gde Pujaastawa; I Gede Adi Sudi Anggara; Ngakan Putu Darma Yasa (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to obtain an ideal concept structure for the online learning model for the practicum category, especially those related to animation learning with 3-dimensional (3D)-based assets. The research was carried out through methodological steps which included collecting data through literature studies and observing online learning assets, specifically in the practicum category and in the field of multimedia design. The design of the selected learning assets is audio-visual learning assets as the most relevant model for online practicum learning. From the results of tests carried out with the user (student) satisfaction test model, in 4 classes of 3D Animation courses at Institut Bisnis dan Teknologi Indonesia (INSTIKI), it was found that the level of student satisfaction with the implementation of 3D Animation online practicum lectures was in the Average grade. The level of student satisfaction illustrates that the 3D Animation practicum model course with all its shortcomings can still run quite well even though it has not reached the ideal level.